Influence of the Interplanetary Convective Electric Field on the Distribution of Heavy Pickup Ions Around Mars. Issue 1 (24th January 2018) - Johnson, B. C.; Liemohn, M. W.; Fränz, M.; Ramstad, R.; Stenberg Wieser, G.; Nilsson, H.
Abstract: This study obtains a statistical representation of 2–15 keV heavy ions outside of the Martian‐induced magnetosphere and depicts their organization by the solar wind convective electric field ( E SW ). The overlap in the lifetime of Mars Global Surveyor (MGS) and Mars Express (MEX) provides a period of nearly three years during which magnetometer data from MGS can be used to estimate the direction of E SW in order to better interpret MEX ion data. In this paper we use MGS estimates of E SW to express MEX ion measurements in Mars‐Sun‐Electric field (MSE) coordinates. A new methodological technique used in this study is the limitation of the analysis to a particular instrument mode for which the overlap between proton contamination and plume observations is rare. This allows for confident energetic heavy ion identification outside the induced magnetosphere boundary. On the dayside, we observe high count rates of 2–15 keV heavy ions more frequently in the + E SW hemisphere (+ Z MSE ) than in the − E SW hemisphere, but on the nightside the reverse asymmetry was found. The results are consistent with planetary origin ions being picked up by the solar wind convective electric field. Though a field of view hole hinders quantification of plume fluxes and velocity space, this new energetic heavy ion identification technique means that Mars Express should prove useful in expanding the time period available to assess general plume loss variation with drivers. Plain Language Summary: The location and flow direction of oxygen escaping Mars' atmosphere is organized by a global‐scale electric field associated with the Sun's flowing magnetic field. While the Mars Express (MEX) satellite is less well equipped than Mars Atmosphere and Volatile Evolution (MAVEN) to estimate exact flux values of ions accelerated by this electric field, our demonstration that MEX can see this population statistically opens a new window of time (pre‐MAVEN) to studies of the variability of this atmospheric escape channel. Key Points: Mars Express heavy ion data outside the magnetic boundary show a statistical asymmetry consistent with other energetic plume studies The energetic plume is more prevalent on the dayside (i.e., X > 0), while for X < 0 higher count rates in the + E SW direction were not seen For a specific instrument setting, overlap between proton contamination and the plume is rare, allowing for confident plume identification